Pelatihan Pembuatan Nata de Tomato sebagai Pangan Fungsional untuk Mendukung Camilan Sehat dalam Upaya Pencegahan Stunting di Desa Sukatepu, Kabupaten Karo, Sumatera Utara - Asti Dewianti Silalahi; Fahrozi Fahrozi; Shella Febrina Lubis; Muhammad Reza Saputra; Sry Rahayu Ningsih Sitorus; Muhammad Nuh (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Stunting remains a serious public health problem worldwide. Globally, its prevalence reaches 23.2%, while in Indonesia in 2024 it was recorded at 19.8%. The situation in Sukatepu Village is even more alarming, with 43.5% of children aged 24-50 months affected. This figure far exceeds the 20% threshold set by WHO, highlighting the urgent need for effective interventions, especially those utilizing local food resources. One promising approach is the use of tomatoes, a fruit rich in vitamins, minerals, fiber, and antioxidants. Through this community service program, tomatoes were processed into a healthy, low-sugar snack called Nata de Tomato using Acetobacter xylinum fermentation. The program aimed not only to increase family nutrition knowledge but also to equip the community with practical skills to produce functional foods that can help improve children's nutritional intake.The program engaged 23 participants, including teenage girls, posyandu (community health post) cadres, and housewives. Activities involved nutrition education, hands-on training in Nata de Tomato production, and sensory testing to evaluate product acceptance. Results were encouraging: 80% of participants successfully produced Nata de Tomato according to standard procedures, their understanding of nutrition significantly improved, and nearly 95% of tasters reported liking the product's taste, aroma, color, and texture. Overall, processing tomatoes into Nata de Tomato shows strong potential as a community-based nutrition intervention to prevent stunting while promoting healthier eating habits using local food resources.